A systematic conservation planning approach to fire risk management in Natura 2000 sites. (1st October 2016) - Foresta, Massimiliano; Carranza, Maria Laura; Garfì, Vittorio; Di Febbraro, Mirko; Marchetti, Marco; Loy, Anna
Abstract: A primary challenge in conservation biology is to preserve the most representative biodiversity while simultaneously optimizing the efforts associated with conservation. In Europe, the implementation of the Natura 2000 network requires protocols to recognize and map threats to biodiversity and to identify specific mitigation actions. We propose a systematic conservation planning approach to optimize management actions against specific threats based on two fundamental parameters: biodiversity values and threat pressure. We used the conservation planning software Marxan to optimize a fire management plan in a Natura 2000 coastal network in southern Italy. We address three primary questions: i) Which areas are at high fire risk? ii) Which areas are the most valuable for threatened biodiversity? iii) Which areas should receive priority risk-mitigation actions for the optimal effect?, iv) which fire-prevention actions are feasible in the management areas?. The biodiversity values for the Natura 2000 spatial units were derived from the distribution maps of 18 habitats and 89 vertebrate species of concern in Europe (Habitat Directive 92/43/EEC). The threat pressure map, defined as fire probability, was obtained from digital layers of fire risk and of fire frequency. Marxan settings were defined as follows: a) planning units of 40 × 40 m, b) conservation features defined as all habitats and vertebrate species of European concern occurring in the study area, c) conservation targets defined according with fire sensitivity and extinction risk of conservation features, and d) costs determined as the complement of fire probabilities. We identified 23 management areas in which to concentrate efforts for the optimal reduction of fire-induced effects. Because traditional fire prevention is not feasible for most of policy habitats included in the management areas, alternative prevention practices were identified that allows the conservation of the vegetation structure. The proposed approach has potential applications for multiple landscapes, threats and spatial scales and could be extended to other valuable natural areas, including protected areas. Highlights: Systematic conservation planning for the management of biodiversity threats. Wildfire prevention based on costs derived from fire probability. Biodiversity values derived from policy habitats and species into Natura 2000 sites. Map of 23 irreplaceable biodiversity areas where fire prevention is needed. Fire management inside policy habitats designed to preserve the vegetation structure.